Joint toxic effects of thiamethoxam and flusilazole on the adult worker honey bees (Apis mellifera L.). (15th January 2023) - Wang, Dou; Lv, Lu; Gao, Zhongwen; Zhu, Yu-Cheng; Weng, Hongbiao; Yang, Guiling; Wang, Yanhua
Abstract: Insect pollinators are routinely exposed to a complex mixture of many pesticides. However, traditional environmental risk assessment is only carried out based on ecotoxicological data of single substances. In this context, we aimed to explore the potential effects when worker honey bees ( Apis mellifera L.) were simultaneously challenged by thiamethoxam (TMX) and flusilazole (FSZ). Results displayed that TMX possessed higher toxicity to A. mellifera (96-h LC50 value of 0.11 mg a. i. L −1 ) than FSZ (96-h LC50 value of 738 mg a. i. L −1 ). Furthermore, the mixture of TMX and FSZ exhibited an acute synergistic impact on the pollinators. Meanwhile, the activities of SOD, caspase 3, caspase 9, and PPO, as well as the expressions of six genes ( abaecin, dorsal-2, defensin-2, vtg, caspase-1, and CYP6AS14 ) associated with oxidative stress, immune response, lifespan, cell apoptosis, and detoxification metabolism were noteworthily varied in the individual and mixture challenges than at the baseline level. These data revealed that it is imminently essential to investigate the combined toxicity of pesticides since the toxicity evaluation from individual compounds toward honey bees may underestimate the toxicity in realistic conditions. Overall, the present results could help understand the potential contribution of pesticide mixtures to the decline of bee populations. Graphical abstract: Image 1 Highlights: Thiamethoxam showed a higher acute toxic effect on the honey bees than fluconazole. Thiamethoxam in combination with fluconazole produced synergistic toxicity. CYP450s had important roles in the synergism of fluconazole and thiamethoxam. mRNA levels of 6 genes in mixtures elicited greater alterations than individuals. Joint effects should be incorporated into ecological risk assessment of pesticide.